HIGH CIRCULATING LEVEL OF FIBROBLAST GROWHT FACTOR-23 PROMOTES RENAL EXCRETION OF PHOSPHATE IN HEMODIALYSIS PATIENTS WITH RESIDUAL RENAL FUNCTION - Mengjing Wang; Li You; Haiming Li; Yong Lin; Zhijie Zhang; Chuanming Hao; Jing Chen (The Korean Society of Nephrology, 2012)
Fibroblast growth factor-23 (FGF-23) regulates phosphate metabolism and elevated levels occur in patients with kidney disease and are associated with smortality in maintenance hemodialysis (MHD) patients. Residual renal function (RRF) presumably improves phosphate metabolism in MHD patients. We investigated the role of circulating FGF-23 on urinary phosphate excretion and phosphate balance in 134 MHD patients. Demographics, laboratory data, and excretion capacity of phosphate were recorded. We used multivariable regression to analyze the relationship of serum phosphate with other factors and of the tubular reabsorption rate of phosphate with other factors. Patients with high urinary output (>200 mL/day) had lower serum phosphate, calcium, iPTH, and FGF-23 than patients with low urinary output (< 200 mL/day). The independent risk factors for elevated serum phosphate were nPNA, iPTH, and FGF-23 in patients with low urinary output, and female gender and GFR in patients with high urinary output. In high urinary output patients, the weekly phosphate excretion was 300 to 1500 mg, the renal contribution to weekly phosphate elimination was about 15% when GFR < 2 mL/min, 25% when 2≤ GFR < 5 mL/min, and 40% when GFR ≥ 5 mL/min. The tubular reabsorption of phosphate (44% ± 19%) was nearly 50% of the normal level, much lower than that of sodium, chlorine, and calcium which ranged from 85% to 99%. Elevated circulating FGF-23 was significantly associated with decreased tubular phosphate reabsorption after adjusting for GFR and serum phosphate (β=-0.147, p=0.003). In conclusion, RRF is associated with significant capacity to excrete phosphate and high levels of FGF-23 promote phosphate excretion in remnant nephrons.